Endoscopic submucosal resection of esophageal subepithelial lesions using band ligation - Lee, D. G.; Kim, G. H.; Park, D. Y.; Jeong, J. H.; Moon, J. Y.; Lee, B. E.; Hosuk, I.; Song, G. A. (Endoscopy, 2011)
Subepithelial lesions (SELs) are occasionally found in the esophagus during upper endoscopy. Sometimes endoscopic resection is needed for accurate diagnosis or in the rare cases of malignant transformation of SELs. In this case series, we evaluated the usefulness of endoscopic submucosal resection with a ligation device (ESMR-L) in esophageal SELs. Twenty-three patients with 25 esophageal SELs that were no larger than 13 mm and were localized within the muscularis mucosae or submucosa were enrolled. ESMR-L was successfully performed in all 25 SELs. The en bloc resection rate was 100% (25/25), and histologically complete resection was achieved in 24 lesions (24/25, 96%). After resection of the lesion by snare, minor immediate bleeding occurred in four cases, but there was no delayed bleeding or perforation.